Efficacy and Safety of Antithrombotic Therapy With Oral Anticoagulants in Real-World Elderly Patients With Acute Coronary Syndrome and Atrial Fibrillation - Wu, Yangxun; Liu, Haiping; Qin, Liu'an; Wang, Yuyan; Zhang, Shizhao; Wang, Ziqian; Zou, Yuting; Yin, Tong (Frontiers in Cardiovascular Medicine, 2022)
Background: The efficacy and safety of antithrombotic treatment with oral anticoagulants (OACs) in elderly patients with comorbidities of acute coronary syndrome (ACS) and atrial fibrillation (AF) are unclear. Methods: A cohort of hospitalized elderly patients (≥ 65 years of age) diagnosed with ACS and AF and treated with oral antithrombotic agents were consecutively recruited. Follow-up was performed for at least 1 year. Major adverse cardiac events (MACEs) were defined as a composite of all-cause death, nonfatal myocardial infarction (MI), nonfatal stroke, and systemic embolism. The safety outcomes of bleeding were defined according to the Bleeding Academic Research Consortium (BARC) criteria. Results: A cohort of 548 eligible patients (76 ± 6.6 years) was analyzed. Compared to the patients with OAC treatment (n=184, 33.6%), patients treated without OAC (n=364, 66.4%) were older, had a lower prevalence of persistent AF and unstable angina (UA), and more often presented with paroxysmal AF, acute myocardial infarction (AMI), stent implantation and dual antiplatelet therapy (DAPT). Compared to the patients without OAC treatment (n=364, 66.4%), patients treated with OAC (n=184, 33.6%) had a lower risk of MACEs at both the 1-year (4.3% vs. 15.1%, adjusted HR: 0.34, 95% CI: 0.15-0.80, p = 0.014) and 5-year (17.5% vs. 48.4%, adjusted HR: 0.36, 95% CI: 0.19-0.67, p = 0.001) follow-up. No significant difference was observed for bleeding events of BARC ≥ 2 between the groups (8.0% vs. 9.0%, adjusted HR: 1.17, 95% CI: 0.58-2.34, p = 0.667). Compared with warfarin-treated patients, the non-vitamin K antagonist oral anticoagulant-treated patients had lower risks of all-cause mortality (2.1% vs. 9.5%, HR: 0.18, 95% CI: 0.03-0.98, p = 0.047) and bleeding events of BARC ≥ 3 (2.1% vs. 4.8%, HR: 0.14, 95% CI: 0.02-1.10, p = 0.062). Conclusions: Antithrombotic therapy with OACs in elderly patients with ACS and AF was associated with a lower risk of ischemic events without an increase in bleeding events. In real-world practice, the clinical awareness of anticoagulation treatments in elderly patients with ACS and AF needs to be strengthened.